AI-Based Linguistic Frameworks for Monitoring Physical Health, Sports Performance, and Educational Contexts - Rakhimov Vladimir; Saidnazarov Ulugbek; Mustafaev Ispandiyar (SHS Web of Conferences)
Advancements in discourse analysis techniques on health and sports data streams are challenging traditional conceptions of diagnostic validity and educational feedback systems, and in the process, opening up windows of opportunity for redefining the interpretive logics associated with language-mediated monitoring systems. As little is known about where computational linguistics-based health inference is gaining momentum beyond clinical diagnostics and performance analytics, the purpose of this study is to map in what clusters of application domains it is perceived to gain traction. Drawing on data from network-based visualizations and structural equation models in multimodal datasets, we identify a long tail of embedded constructs and relational dependencies in which a total of 76 unique conceptual nodes operate, including predictors such as lexical calibration, contextual sentiment attribution, and semantic load dispersion. Our findings reveal a strong, positive correlation coefficient (r = 0.82) between semantic coherence and predictive decision consistency. However, target users do not passively comply. Rather, their perceptual feedback loops and adaptive interpretations are integrated into the iterative refinement of monitoring algorithms. The paper concludes by identifying emerging linguistic bottlenecks, reflecting on the application of AI-driven linguistic inference in the field of education and sports physiology, and proposing suggestions for scalable framework deployment. The resulting insights enrich understandings of the workings of semantic computing architectures in experiences of personalized health diagnostics and intelligent educational environments.